Attitudes Towards Drug Policies in Latin America: Results from a Latin-American Survey - Mendiburo-Seguel, A (Elsevier B.V., 2017)
Background In recent years Latin American countries have increasingly rejected the traditional prohibitionist paradigm of drug policy, reflecting its failure to reduce either consumption or trafficking. The extent to which these policy trends currently command pubic support is unclear, however. This article goes some way to filling this gap, providing a snapshot of public attitudes towards drug policies in nine Latin American countries. Methods The 2014 Annual Survey of the Observatory of Drug Policies and Public Opinion, which has representative population samples, was used to measure public opinion. Country comparisons are made using descriptive and inferential statistics. Results Countries fall into three groups: Peru, Bolivia and El Salvador are the most conservative countries on drug policy and perceptions of risks of cannabis use; they also score lowest on Human Development Index. On the other hand, the public in Chile and Uruguay are more likely to support drug policy reform. The remaining four countries (Argentina, Colombia, Mexico and Peru) tend to occupy the middle ground between these extremes. In addition, cannabis legalization is explained by its recreational use, being this the main meaning attached to cannabis policy among Latin American citizens. Conclusion There is a significant heterogeneity in attitudes towards drug policies in Latin American countries, which suggests that people are questioning the policies that set the norm in Latin America without achieving any consensus regarding future measures for each country. © 2016 Elsevier B.V.